Quit rates and predictors of smoking abstinence in Thai Buddhist monks with noncommunicable diseases - Wiwat Laochai; Sunida Preechawong (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of this study is to calculate the smoking quit rate and to examine the factors influencing smoking abstinence among Thai Buddhist monks with noncommunicable diseases (NCDs). Design/methodology/approach - This was a cross-sectional study of 136 Buddhist monks with NCDs purposively sampled from the Priest Hospital. The participants were between 20 and 59 years of age, smoked at least one cigarette a day and received cessation advice from nurses or other health professionals. The dependent variable was self-reported 7-day point-prevalence smoking abstinence assessment at a three-month follow-up. Independent variables were age, schooling level, nicotine dependence, intention to quit, physical activity and perceived self-efficacy in quitting cessation. Logistic regression was performed to evaluate the factors influencing smoking cessation. Findings - 50 of the 136 Thai Buddhist monks (36.8%) reported the 7-day point prevalence abstinence at a three-month follow-up. About two-thirds of the participants indicated health concern as the motivation to quit smoking. Perceived self-efficacy of abstinence (odds ratio 1.04; 95% confidence interval 1.014-1.074) and intention to quit smoking (odds ratio 1.34; 95% confidence interval 1.129-1.599) were significant predictors of abstinence. Originality/value - This is the first study of its kind to investigate the predictors of smoking cessation in Thai Buddhist monks with NCDs. The findings will be of help to healthcare counselors seeking to motivate monks to quit smoking.